2016
DOI: 10.3390/v8100270
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Hepatitis E Virus: Classification, Animal Reservoirs and Transmission Routes

Abstract: During the past ten years, several new hepatitis E viruses (HEVs) have been identified in various animal species. In parallel, the number of reports of autochthonous hepatitis E in Western countries has increased as well, raising the question of what role these possible animal reservoirs play in human infections. The aim of this review is to present the recent discoveries of animal HEVs and their classification within the Hepeviridae family, their zoonotic and species barrier crossing potential, and possible u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
209
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(216 citation statements)
references
References 188 publications
(272 reference statements)
3
209
0
4
Order By: Relevance
“…In 1997, Meng et al [140] reported for the first time the detection of the virus in pigs in the United States. Since then, HEV has been isolated from different species such as deer, wild boar, monkey, mongoose, rabbit, ferret, trout, bat, rat, chicken, kestrel, falcon, camel, and trout [141]. However, only pigs, wild boars, and deer are considered true reservoirs of the virus for humans [142].…”
Section: Hev In Animalsmentioning
confidence: 99%
“…In 1997, Meng et al [140] reported for the first time the detection of the virus in pigs in the United States. Since then, HEV has been isolated from different species such as deer, wild boar, monkey, mongoose, rabbit, ferret, trout, bat, rat, chicken, kestrel, falcon, camel, and trout [141]. However, only pigs, wild boars, and deer are considered true reservoirs of the virus for humans [142].…”
Section: Hev In Animalsmentioning
confidence: 99%
“…Genotypes 1 and 2 exclusively affect humans and are the cause of large epidemics. Although HEV genotype 3 has been isolated in many animals, pigs constitute the main viral reservoir . The consumption of raw or undercooked pork products has been established as one of the main routes of transmission of infection to humans .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a phylogenetic analysis has demonstrated that human and swine HEV strains isolated from the same regions share high sequence identities of up to 91.3%–100%, suggesting a close phylogenetic relationship (Liu et al, ). Experimental cross‐species transmission of HEV has also been confirmed across humans, non‐human primates and swine with genotypes 3 and 4 (Doceul, Bagdassarian, Demange, & Pavio, ).…”
Section: Introductionmentioning
confidence: 94%